A Cross-sectional Online Survey on Public Attitudes towards Wearing Face Masks and Washing Hands to Prevent the Spread of COVID-19 in Indonesia - Rumahorbo, Hotma; Priyanto, Priyanto; Karjatin, Atin (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The COVID-19 infection spreads quickly and easily, hence people are required to obey health protocols. Attitudes play an important role in building people’s readiness to use face masks and wash hands. AIM: The study aims at analyzing several factors influencing people’s attitudes towards wearing face masks and washing hands in Indonesia. METHODS: The study employs a cross-sectional online survey involving 400 adult respondents in the Java region from July to September 2020. RESULTS: Of 400 respondents, 54.3% showed positive attitudes toward wearing face masks and 59.3% towards washing hands. The multivariate analysis showed that people’s attitudes towards wearing face masks were influenced by age and knowledge. Respondents aged 36–45 years old had positive attitudes on wearing face masks 3.9 times (p = 0.038) and aged ≥46 years old 4.1 times (p = 0.039) compared to aged 18–35 years old. Furthermore, attitudes on washing hands were influenced by gender, age groups, and knowledge. Female had positive attitudes towards washing hands 1.7 times (p = 0.029) compared to male. Respondents aged 36–45 years old had positive attitudes on washing hands 5 times (p = 0.037) and aged ≥46 years old 4.8 times (p = 0.05) compared to aged 18–35 years old. Knowledge acted as the confounding factor. CONCLUSION: The age and knowledge factors influenced positive attitude of using masks and washing hands were influenced by gender, age, and knowledge. Health education programs are recommended to increase knowledge about COVID-19, this is very helpful for the young generation of Indonesia to have a positive attitude.